Recognition of taxes and implementation of tax procedures by SMEs in Albania - Etleva Bajrami (Contemporary Economics, 2021)
In Albania, most businesses are classified as SMEs and their importance in the economy has grown exponentially in recent years. As SMEs comprise the majority of businesses, their taxes are crucial for the state budget. The purpose of this paper is to understand the SMEs' attitude toward tax compliance. The objective of this research is to assess tax knowledge of SMEs as a precondition for tax compliance. Tax noncompliance has been a prevalent issue, and the tax authorities have undertaken a reform in this regard. This paper aims to understand the current situation regarding tax compliance. The current study is based on questionnaires distributed to 348 SMEs. Businesses responded to questions related to the recognition of taxes, duties and procedures. SMEs are separated in two groups, small and medium by annual turnover, in order to achieve the most accurate survey results. The results of the questions were not always the same for both groups. There are more small businesses that are not familiar with taxes, duties and tax procedures, resulting in conclusion that medium businesses are more tax compliant than small businesses. Tax authorities need to know the situation of SMEs, get their opinions on taxes and duties and take them into consideration.
Keywords: H26; E62; H32; 330; SME; compliance; taxes; Albania